IMPLEMENTASI SISTEM PENENTUAN NILAI BANTUAN PENYALURAN ZIS (ZAKAT, INFAQ, SEDEKAH) DENGAN METODE ANALYTICAL HEIRARCHY PROSES (AHP) - Putra, Syahrizal Dwi; Malabay, Malabay; Aryani, Diah (Jurnal EDik Informatika, 2020)
The distribution of Zakat, Infak Sedekah (ZIS) funds must be given to recipients who are worthy and deserving of it by allocating funds in accordance with the provisions in the Unit Pelayanan Zakat (UPZ). Data processing for potential beneficiaries is still done manually, so it takes a long time and is a complicated process to update or calculate the evaluation criteria for potential beneficiaries. Based on the above problems, the researcher provides a solution by designing a decision support system for selecting recipients of ZIS assistance using the Analytic Hierarchy Process (AHP) method. The result of this research is a web application to make it easier for the UPZ admin to make proposals for ZIS assistance recipients because the priorities of each mustahik who submit requests for assistance have been determined so that the process of determining the priority of each mustahik who will receive ZIS assistance can be faster, more objective and measurable.